2013
DOI: 10.1016/j.eats.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic All-Inside Anterior Cruciate Ligament Reconstruction Using the Translateral Technique

Abstract: There is growing evidence that anatomic placement of the femoral tunnel in anterior cruciate ligament reconstruction confers biomechanical advantages over the traditional tunnel position. The anteromedial portal technique for anatomic anterior cruciate ligament reconstruction has many well-described technical challenges. This article describes the translateral all-inside technique, which produces anatomic femoral tunnel placement using direct measurement of the medial wall of the lateral femoral condyle and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 18 publications
0
49
0
1
Order By: Relevance
“…All-inside ACL reconstruction facilitates anatomic placement of the graft. 15,16 This more accurately replicates the biomechanics of the native ACL and more accurately restores knee kinematics in comparison to nonanatomic reconstruction. 15,17 Specifically, traditional transtibial graft placement tends to place the femoral tunnel high and deep within the intercondylar notch with respect to the ACL footprint, creating a vertically oriented graft that fails to restore rotational stability.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…All-inside ACL reconstruction facilitates anatomic placement of the graft. 15,16 This more accurately replicates the biomechanics of the native ACL and more accurately restores knee kinematics in comparison to nonanatomic reconstruction. 15,17 Specifically, traditional transtibial graft placement tends to place the femoral tunnel high and deep within the intercondylar notch with respect to the ACL footprint, creating a vertically oriented graft that fails to restore rotational stability.…”
Section: Discussionmentioning
confidence: 88%
“…15,16 This more accurately replicates the biomechanics of the native ACL and more accurately restores knee kinematics in comparison to nonanatomic reconstruction. 15,17 Specifically, traditional transtibial graft placement tends to place the femoral tunnel high and deep within the intercondylar notch with respect to the ACL footprint, creating a vertically oriented graft that fails to restore rotational stability. 18,19 The use of retrograde sockets in lieu of tunnels is boneconserving and minimizes the risk of convergence with the femoral tunnel of the PLC reconstruction.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Anatomically reconstruction of the ACL is considered a gold standard in the world of orthopedics as it provides a facile graft placement, better outcomes and lower pain after surgery. The most common graft used in all-inside technique is the quadrupled semitendinosus tendon, therefore preserving hamstring strength and allowing a faster rehabilitation and return to daily activities [3,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) reconstruction is being performed more than 100.000 times in a year only in the United States [1]. The full tibial tunnel technique is considered a standard technique by many surgeons, whereas in the all-inside technique, the the tibial tunnel is replaced by a tibial socket [2][3][4][5]. Older studies concluded that all-inside technique had a faster rehabilitation time and pain after surgery is slightly diminished [4].…”
mentioning
confidence: 99%